2017
DOI: 10.14341/dm8328
|View full text |Cite
|
Sign up to set email alerts
|

Macular oedema as manifestation of diabetic retinopathy

Abstract: ОфтальмологияOphthalmology иабетическая ретинопатия (ДР) -микрососуди-стое осложнение сахарного диабета (СД) с пер-вичным поражением прекапиллярных артериол, капилляров и посткапиллярных венул с возможным вовле-чением сосудов более крупного калибра и развитием ми-кроаневризм, кровоизлияний, экссудативных изменений, с макулопатией и пролиферацией новообразованных со-судов на глазном дне [1]. В экономически развитых странах одной из ведущих причин слепоты у лиц трудоспособного возраста является ДР, на долю котор… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Timely laser photocoagulation and/or ant-VEGF treatment for severe PDR, particularly in the presence of DME, can prevent further visual loss [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Timely laser photocoagulation and/or ant-VEGF treatment for severe PDR, particularly in the presence of DME, can prevent further visual loss [3].…”
Section: Introductionmentioning
confidence: 99%
“…Others confirmed that laser photocoagulation is still effective for visual loss but does not improve DME. Laser photocoagulation is also aimed at retinal ischemic areas, suppression of neovascularization and obliteration of vessels with increased permeability [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Исследования контроля Сд и его осложнений показали, что диабетический макулярный отек у пациентов с Сд1 в 27 % случаев развивается в течение 9 лет после начала заболевания. У пациентов с Сд2 распространенность макулярного отека также возрастает с увеличением длительности диабета: с 3 % случаев при длительности заболевания менее 5 лет до 28 % при длительности 20 лет и более [2,15].…”
unclassified